A novel technique to improve the compressive strength and ductility of glass fiber reinforced polymer (GFRP) composite bars. (4th April 2022) - Liu, Yue; Zhang, Hong-Tao; Tafsirojjaman, T.; Ur Rahman Dogar, Attiq; AlAjarmeh, Omar; Yue, Qing-Rui; Manalo, Allan
Highlights: Novel technique has been developed to improve compressive strength of GFRP bars. GFRP bars are winded with one, two and three layers of GFRPs in transverse direction. Tensile and compressive strength tests have been conducted to assess the improvement. Theoretical model has been developed to predict the compressive strength of GFRP bar. Abstract: Glass fiber reinforced polymer (GFRP) composite bars have excellent durability compared to traditional steel reinforcements but their strength contribution in the design of compression members is generally neglected. The non-homogeneous and anisotropic nature of GFRP bars including their complex behavior in compression and the lack of standard testing procedure have hindered their use as compressive reinforcements. To improve their behavior and strength in compression, a novel technique has been developed by winding additional GFRP layers around the longitudinal fibers. One, two and three winding layers with a thickness of 1.5 mm for each layer and a winding angle of ± 83.3° have been used. Compressive strength tests have then been conducted on 20 mm and 30 mm high GFRP bars with a core diameter of 20 mm to determine the improvement in compressive strength, ductility, and failure behavior. Test results showed that the 20 mm core diameter GFRP bars have shown promising improvement in the compressive strength and ductility with the increased number of winding layers wherein the compressive strength of the 20 mm and 30 mm high bars increased by 74% and 63%, respectively for bars with three winding layers. Comparison of the mechanical properties in compression and tension showed that the optimum strength and ductility improvement can be achieved with two winding layers. A simple theoretical strength model has been developed which can reliably predict the compressive strength of the winded GFRP bars.